2005
DOI: 10.2176/nmc.45.411
|View full text |Cite
|
Sign up to set email alerts
|

Multi focal Pilocytic Astrocytomas With Ependymal Differentiation in the Bilateral Medial Temporal Lobes-Case Report-

Abstract: A 7-year-old boy presented with headache, visual disturbance, and psychomotor seizures persisting for 7 months. He had mild hemiparesis and homonymous hemianopia on the left. Neuroimaging showed bilateral temporal lobe masses with calcification and cysts. The right temporal mass was subtotally resected. The histological diagnosis was pilocytic astrocytoma with ependymal differentiation and a MIB-1 staining index of up to 8.0%. Postoperatively his hemiparesis and psychomotor seizures disappeared. Adjuvant chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In such cases, early detection of multifocal juvenile pilocytic astrocytoma by MRI may change treatment strategies and improve prognosis [24]. Thus, even though juvenile pilocytic astrocytoma usually presents as a solitary mass in the cerebellum or optic pathway with low proliferative activity, it occasionally presents as multifocal tumor with more aggressive behavior [25,26]. In a study of 90 patients with either primary or recurrent pilocytic astrocytoma, 11 patients developed multicentric spread.…”
Section: Pathologymentioning
confidence: 99%
“…In such cases, early detection of multifocal juvenile pilocytic astrocytoma by MRI may change treatment strategies and improve prognosis [24]. Thus, even though juvenile pilocytic astrocytoma usually presents as a solitary mass in the cerebellum or optic pathway with low proliferative activity, it occasionally presents as multifocal tumor with more aggressive behavior [25,26]. In a study of 90 patients with either primary or recurrent pilocytic astrocytoma, 11 patients developed multicentric spread.…”
Section: Pathologymentioning
confidence: 99%
“…Gilles et al 14 noted parenchymal calcification more among older children, while Philipson et al 30 observed calcification and ossification in a case of PA involving spinal nerve root in a 39-year-old woman. Dierssen et al 11 also described extensive calcification in a case of pontine PA. Maruyama et al 28 and Lee et al 24 reviewed the CT and MR characteristics of juvenile pilocytic astrocytomas and noted tumor calcification in occasional cases.…”
Section: Discussionmentioning
confidence: 99%
“…Other features that are variably present in PA include sclerotic vessels, vascular proliferation, calcification 7,11,14,24,27,28,30 and chronic inflammation, 7,14,27 while nuclear pleomorphism, mitosis and necrosis are rare. Owing to the differences in prognosis and therapeutic options, it is vital to distinguish PA from diffuse astrocytoma, and in the presence of mitosis / necrosis from other high-grade neoplasm.…”
mentioning
confidence: 99%